Assessment of retired elderly’s people autonomy and its affecting factors in Rasht - Nasrin Masoumi; Shirin Jafroudi; Atefeh Ghanbari Khanghah; Ehsan Kazemnejad Leili (Journal of Holistic Nursing and Midwifery)
Introduction: In elderly, autonomy is threatened due to physical and mental disability. This ‎disability in activity of daily living is a chronic condition that causes cost disbursement in ‎society and reduce older people s quality of life.